Exploring procedural justice, obligation to obey and cooperation with the police in a sample of university students - Bello, Paul Oluwatosin (Contemporary justice review, 2021)
This study scrutinizes the applicability of the Tylerian process-based model of regulation to the South African context. In any democracy, the police do not operate in isolation, but rely on public obedience and cooperation for the actualisation of their constitutional responsibilities. Previous studies on obligation to obey and cooperate with the police have focused on the general population with less consideration for specific component of the population, namely, university students. But with the frequent police-students encounters, we are uncertain whether university students will be willing to obey and cooperate with the police or not. Using a sample of 683 participants from a large university in South Africa, we test the effect of both normative and instrumental factors on university students’ obligation to obey, and willingness to cooperate with the police. This current study corroborates previous findings that emphasized willingness to obey and cooperate with the police if the police are procedurally just and effective in discharging their constitutional duties.